Analysing urban ventilation in building arrays with the age spectrum and mean age of pollutants. (March 2018) - Lau, G.E.; Ngan, K.
Abstract: This study investigates the applicability and relevance of the Green's function and age spectrum to urban ventilation. Ventilation in an idealised urban environment is examined by characterising pollutant dispersion from the urban canopy layer. Air flow over regular uniform and non-uniform building arrays is computed using large-eddy simulation and pollutant removal is analysed via the age spectrum for localised sources. The age spectrum represents the probability distribution function of pollutant or tracer ages. Since the age spectrum is obtained directly from the evolution equation for the passive scalar, it is more effective for flows with high intermittency. This should be beneficial for studies of extreme pollution events in the urban environment such as accidental release of toxic gases and dust storms. It is demonstrated that the age spectrum is sensitive to the source release location, implying that pollutant removal depends on the initial conditions. Mean ages calculated using the homogeneous emission method and the age spectrum show qualitative similarities; however, there are quantitative differences in regions where the flow is highly unsteady and intermittent. The age spectrum indicates that ventilation decreases by ∼70% when the aspect ratio (building height/street width) is increased from 1 to 4. Furthermore, the effect of fresh air entrainment increases by ∼80% when the building heights are non-uniform. Highlights: Ventilation in inhomogeneous urban environment is quantified using age spectrum. Pollutant removal shows sensitivity to the source release location. Age spectrum captures the highly intermittent behaviour of the urban flow.